Impact evaluation of a community-based intervention for prevention of cardiovascular diseases in the slums of Nairobi: the SCALE-UP study - Steven van de Vijver; Samuel Oji Oti; Gabriela B. Gomez; Charles Agyemang; Thaddaeus Egondi; Eric Moll van Charante; Lizzy M. Brewster; Catherine Hankins; Zlata Tanovic; Alex Ezeh; Catherine Kyobutungi; Karien Stronks (Taylor & Francis Group, 2016)
Background: A combination of increasing urbanization, behaviour change, and lack of health services in slums put the urban poor specifically at risk of cardiovascular disease (CVD). This study aimed to evaluate the impact of a community-based CVD prevention intervention on blood pressure (BP) and other CVD risk factors in a slum setting in Nairobi, Kenya. Design: Prospective intervention study includes awareness campaigns, household visits for screening, and referral and treatment of people with hypertension. The primary outcome was overall change in mean systolic blood pressure (SBP), while secondary outcomes were changes in awareness of hypertension and other CVD risk factors. We evaluated the intervention's impact through consecutive cross-sectional surveys at baseline and after 18 months, comparing outcomes of intervention and control group, through a difference-in-difference method. Results: We screened 1,531 and 1,233 participants in the intervention and control sites. We observed a significant reduction in mean SBP when comparing before and after measurements in both intervention and control groups, −2.75 mmHg (95% CI −4.33 to −1.18, p=0.001) and −1.67 mmHg (95% CI −3.17 to −0.17, p=0.029), respectively. Among people with hypertension at baseline, SBP was reduced by −14.82 mmHg (95% CI −18.04 to −11.61, p<0.001) in the intervention and −14.05 (95% CI −17.71 to −10.38, p<0.001) at the control site. However, comparing these two groups, we found no difference in changes in mean SBP or hypertension prevalence. Conclusions: We found significant declines in SBP over time in both intervention and control groups. However, we found no additional effect of a community-based intervention involving awareness campaigns, screening, referral, and treatment. Possible explanations include the beneficial effect of baseline measurements in the control group on behaviour and related BP levels, and the limited success of treatment and suboptimal adherence in the intervention group.